ANALYSIS OF THE GARMENT FACTORY INDEPENDENCE DEVELOPMENT PROGRAM IN PREPARING PRISONERS FOR SOCIAL REINTEGRATION AT THE CLASS I MAKASSAR CORRECTIONAL FACILITY - Imasti, Andi Talitha Miranda; Rohayati, Ade Cici (Universitas Nusa Cendana, 2025)
This study aims to analyze the development of independence through the garment factory program at the Makassar Class 1 correctional institution in preparing prisoners to live in society. This program aims to provide work skills to prisoners so that they have sufficient economic provisions and are able to integrate with the community after serving their sentences. Garment factory independence coaching is considered a solution in reducing recidivism rates, because through the sewing skills obtained, prisoners can earn income both while in prison and after release. In this research, the method used is a qualitative approach with interview and observation techniques to relevant sources, such as program participants, prison officers, and third parties who cooperate in coaching. The results show that this independence coaching program has had a positive impact on prisoners, such as increased skills, competitive income, and readiness to live independently in the community. However, there are still a number of obstacles, such as limited raw materials and labor regeneration when prisoners are released. Therefore, improvements in management and broader support are needed to ensure the sustainability of this program. Keywords: Independence Development; Garment Factory; Recidivism; Rehabilitation; Social Reintegration; Prisoners